Uso de aditivos e adaptação para dietas com alta inclusão de grão de milho inteiro de bovinos confinados - Mobiglia, Andrea de Mello (2017)
The objective was to evaluate the effects of antimicrobial additives and the inclusion of roughage during adaptation period in diet containing whole shelled corn (WSC, 85% WSC + 15% pelleted concentrate) on performance of Zebu bulls (Exp. 1). The Exp. 1 was realized in randomized complete block design with 2x2 factorial and five replicates. A hundred bulls were fed for 105 d with diet containing monensin (MON, 30 mg/kg DM) ou virginiamycin (VM, 25 mg/kg DM) and with or without inclusion of sugarcane bagasse as roughage (ROU or NO-ROU) in adaptation period. The Exp. 2 was parallel conducted in randomized design with two treatments (MON, 30 mg/kg DM or VM, 25 mg/kg DM) and five replicates. Ten fistulated steers were used and fed with the same diet than Exp. 1 without inclusion of roughage. A laboratorial experiment (Exp. 3) was realized at Kansas State University and its objective was to evaluate the capacity of Megasphaera elsdenii (ME) strain 41125 metabolizes a range of alternative substrates as carbon source. The experiment was designed in randomized complete blocks with six replicates. Viable cell counting, pH, and optical density were measured in media containing glucose, fructose, galactose, arabinose, xylose, maltose, sucrose, lactose, lactate, trehalose, raffinose, Fructooligosaccharide, potato starch, soy protein, succinate. In Exp. 1 and Exp. 2, antimicrobial additives, MON and VM, added to diet containing 85% WSC and 15% pellet concentrate had equal results for performance, ruminal fermentation, and apparent total tract digestibility of nutrients (P≥0.05). However, lower intake was observed in animals fed with monensin includes on diet (P≤ 0.027). Although the additive used had no effect on performance on Exp. 1, the inclusion of roughage in adaptation period showed tendentiously greater final body weight, average daily gain, and efficiency (P≤ 0.088; P≤ 0.075 e P≤ 0.094, respectively) for adaptation period (1 to 20 d) and entire feedlot period (1 to 105 d). There were no treatment effects and interactions for carcass characteristics as hot carcass weight, dressing percentage, carcass daily gain (P≥0.05). In Exp. 3, Megasphaera elsdenii was able to metabolize alternative substrates as glucose, maltose, lactate, Fructo-oligosaccharide, and fructose. However, ME had greater growth in media containing fructose, but the viable cell counting did not show consistent results with optical density. Investigations must be done to clarify the ME metabolism when fructose is used as carbon source. Accord to results obtained in this study, a roughage sorce might be included on adaptation period in diet contenting 85% whole flint corn plus 15% concentrate pellete to obtain greater animal performance. Thus, Megasphaera elsdenii is able to use alternative substrates as lactate, glucose, fructose, and maltose, maintaining their population in rumen.